Perlindungan Hukum bagi Pekerja Akibat Pemutusan Hubungan Kerja pada Masa Pandemi Covid-19 - Eggy Septyadi Silaban; Desak Geded Dwi Arini; Luh Putu Suryani (Warmadewa Press, 2021)
Currently, any part of the world is facing a virus called Covid-19. Since the emergence of this case, all access has been hampered, especially in the economic field. Increasing unemployment is one of the current problems, for that we need a legal protection to ensure life for workers during this pandemic. The purpose of this study to analyze. Arrangements for termination of employment for workers due to the COVID-19 pandemic as well as legal protection for workers due to termination of employment due to the COVID-19 pandemic. This research is a type of normative legal writing with a conceptual approach and legislation. Sources of data used in the form of secondary and primary data sources. Data collection techniques by classifying primary legal materials with secondary legal materials as research support. The analysis of legal materials obtained by qualitative analysis. The results of the study indicate that Termination of Employment has a negative impact on workers because they lose their jobs so that it also has an impact on increasing the poverty level of the Indonesian people. Because the emergence of PSBB regulations from the government of course makes the space for work narrower and layoffs are increasingly prevalent, therefore the regulation of Law no. 13 of 2003 concerning Manpower and also the role of the government is very important to overcome the occurrence of layoffs that are not in accordance with the laws and regulations. The legal protection is divided into 2 things, namely preventive legal protection and repressive legal protection.